Gateways; T1 ( Student's book ) - Victoria Kimbrough (Oxford Univ. Press, 1998)
The book features core vocabulary, acarefully structured grammar syllabus, cross-cultural topics, key learning strategiesintegrated into each unit and consolidated in the Strategy Session review units